2016
DOI: 10.5812/aapm.40106
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Electroacupuncture Reduces Postoperative Pain, Analgesic Requirement and Prevents Postoperative Nausea and Vomiting in Gynaecological Surgery: A Randomised Controlled Trial

Abstract: BackgroundElectroacupuncture (EA) is believed to modulate the pain pathway via the release of endogenous opioid substances and stimulation of descending pain inhibitory pathways. In this study, the use of intraoperative 2 Hertz EA stimulation is investigated to determine any opioid-sparing effect and reduction of postoperative nausea and vomiting (PONV) in patients undergoing gynaecological surgery.Patient and MethodsThis was a prospective, double blinded randomized study conducted in a tertiary hospital in Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Acupoint electrical stimulation has been proven to have obvious analgesic and sedative effects, which can enhance immune function and reduce postoperative complications, such as pain, and nausea and vomiting, which could improve postoperative sleep quality and promote the recovery of patients. 31 , 32 According to previous studies about the analgesic effect of stimulation at ST-36 (Zusanli) and LI-4 (Hegu) acupoints, 33 , 34 we used these two acupoints in combination with PC6 (Neiguan) and HT7 (Shenmen) acupoints after surgery in our study. Thirty minutes of TEAS treatment was also performed bilaterally by an experienced acupuncturist at these four acupoints on the first three nights after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Acupoint electrical stimulation has been proven to have obvious analgesic and sedative effects, which can enhance immune function and reduce postoperative complications, such as pain, and nausea and vomiting, which could improve postoperative sleep quality and promote the recovery of patients. 31 , 32 According to previous studies about the analgesic effect of stimulation at ST-36 (Zusanli) and LI-4 (Hegu) acupoints, 33 , 34 we used these two acupoints in combination with PC6 (Neiguan) and HT7 (Shenmen) acupoints after surgery in our study. Thirty minutes of TEAS treatment was also performed bilaterally by an experienced acupuncturist at these four acupoints on the first three nights after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Seevaunnamtum et al investigated the effect of intraoperative electroacupunctureon the prevention of PONV in 64 female patients undergoing gynaecological surgery. The results of this study reveals that the incidence of PONV was reduced in the electroacupuncture group compared to the control group ( 28 ).…”
Section: Discussionmentioning
confidence: 65%
“…The included studies involved 1117 subjects who received gynecological surgery. Seven studies [ 22 , 23 , 25 – 27 , 32 , 33 ] reported the effects of EA on postoperative gastrointestinal function recovery for patients undergoing total abdominal hysterectomy, and eleven studies [ 21 , 24 , 28 – 31 , 34 – 38 ] involved laparoscopic surgery. Anesthesia type included general anesthesia and epidural anesthesia [ 25 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Anesthesia type included general anesthesia and epidural anesthesia [ 25 , 33 ]. In addition, EA was performed at 24 h prior to surgery in three studies [ 16 , 21 , 30 ], at 30 min prior to surgery or before the start of surgery in ten studies [ 22 , 24 , 28 , 29 , 31 , 34 – 38 ], and after surgery in five studies [ 23 , 25 , 27 , 32 , 33 ]. Among all the acupoints involved in the included studies, Zusanli (ST36) (14/18) and Neiguan (PC6) (11/15) were most frequently selected, while less frequently selected acupoints included Hegu (LI4) (4/18), Shangjuxu (ST37) (3/18), Zhongwan (RN12) (3/18), Tianshu (ST25) (3/18), Liangqiu (ST34) (2/18), Sanjinjiao (SP6) (2/18), Liangmen (ST21) (2/18), Xuehai (SP10) (1/18), and Taichong (LR3) (1/18).…”
Section: Resultsmentioning
confidence: 99%